2021
DOI: 10.1186/s42358-021-00223-2
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with anxiety and depression in rheumatoid arthritis patients: a cross-sectional study

Abstract: Background The management of anxiety and depression symptoms in rheumatoid arthritis (RA) patients is vital. Previous study findings on this topic are conflicting, and the topic remains to be thoroughly investigated. This study aimed to clarify the association of RA disease activity with anxiety and depression symptoms after controlling for physical disability, pain, and medication. Methods We conducted a cross-sectional study of RA patients from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
(80 reference statements)
2
9
0
1
Order By: Relevance
“…We also confirmed the studies that showed the association of depression and anxiety with physical dysfunction (Jamshidi et al, 2020;Uda et al, 2021), being described that the association of moderate to severe depression with physical dysfunction is independent of disease activity (Isnardi et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also confirmed the studies that showed the association of depression and anxiety with physical dysfunction (Jamshidi et al, 2020;Uda et al, 2021), being described that the association of moderate to severe depression with physical dysfunction is independent of disease activity (Isnardi et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In women with RA, an association of depression with all components of the Clinical Disease Activity Index was observed, which also does not include laboratory markers of inflammation (Sautner, Puchner, Akin, &Pieringer, 2020). However, some authors have not demonstrated an association between depression and disease activity when assessed using the DAS-28 (Jamshidi et al, 2016;Juáres-Rojop et al, 2020;Uda et al, 2021). Others showed a significant association of depression only with subjective components of the DAS-28, such as the number of painful joints and global health assessment, both in cross-sectional studies (Michelsen et al, 2017) and after one year of treatment (Boer, Huizinga, & van der Helm-van Mil, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One previous study indicated that depression and anxiety rates are 50.3 and 25.3% in RA patients, respectively [ 12 ]. In another study, 17.6% of RA patients had anxiety and 27.7% of RA patients had depression [ 26 ]. Partly in line with these studies, we reported that the anxiety and depression rates were 29.4 and 29.4% according to the SAS/SDS questionnaire and 36.9% and 36.3% according to the HADS questionnaire, respectively, which were notably higher than those in HCs.…”
Section: Discussionmentioning
confidence: 99%
“…17 The inclusion and measurement of clinical variables varied considerably across the studies. The following variables were found to be associated with higher levels of anxiety: greater disease activity, 26,27,30,31,34,36,41,47,50,52 greater functional disability, 15,19,22,28,30,40,45,46,51 longer disease duration, 30,46,52,56 pain, 19,22,27,28,31,43,45,46,55 fatigue, 31,33 use of medication for pain, 26 use of anti-tumor necrosis factor medications, 57 rheumatoid factor seropositivity, 52 presence of nodules, 52 inflammation measured by erythrocyte sedimentation rate, 26 lower levels of immunoglobulin A, 56 and overall worse physical health. 26 In relation to other comorbid psychiatric conditions, 27 studies examined an association between anxiety and depression, with 14 of those reporting depression to be significantly associated with anxiety.…”
Section: Synthesis Of Measuresmentioning
confidence: 99%